Question
upstudy study bank question image url

Solve the equation. \( \frac{4}{w^{2}+2 w-8}+\frac{5}{w^{2}+w-6}=\frac{4}{w^{2}+7 w+12} \)

Ask by Campbell Long. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( w = -8 \)

Solution

To solve the equation: \[ \frac{4}{w^{2} + 2w - 8} + \frac{5}{w^{2} + w - 6} = \frac{4}{w^{2} + 7w + 12} \] **Step 1: Factor the Denominators** 1. **Factor \( w^{2} + 2w - 8 \):** \[ w^{2} + 2w - 8 = (w + 4)(w - 2) \] 2. **Factor \( w^{2} + w - 6 \):** \[ w^{2} + w - 6 = (w + 3)(w - 2) \] 3. **Factor \( w^{2} + 7w + 12 \):** \[ w^{2} + 7w + 12 = (w + 3)(w + 4) \] **Step 2: Identify the Least Common Denominator (LCD)** The LCD of the denominators \((w + 4)(w - 2)\), \((w + 3)(w - 2)\), and \((w + 3)(w + 4)\) is: \[ \text{LCD} = (w + 4)(w + 3)(w - 2) \] **Step 3: Multiply Both Sides by the LCD** \[ (w + 4)(w + 3)(w - 2) \cdot \left( \frac{4}{(w + 4)(w - 2)} + \frac{5}{(w + 3)(w - 2)} \right) = (w + 4)(w + 3)(w - 2) \cdot \frac{4}{(w + 3)(w + 4)} \] Simplifying each term: \[ 4(w + 3) + 5(w + 4) = 4(w - 2) \] **Step 4: Simplify the Equation** \[ 4w + 12 + 5w + 20 = 4w - 8 \] \[ 9w + 32 = 4w - 8 \] \[ 5w + 32 = -8 \] \[ 5w = -40 \] \[ w = -8 \] **Step 5: Check for Validity** Ensure that \( w = -8 \) does not make any denominator zero: - \( w + 4 = -8 + 4 = -4 \neq 0 \) - \( w - 2 = -8 - 2 = -10 \neq 0 \) - \( w + 3 = -8 + 3 = -5 \neq 0 \) All denominators are non-zero, so \( w = -8 \) is a valid solution. **Final Answer:** \[ w = -8 \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To solve the equation \[ \frac{4}{w^{2}+2 w-8}+\frac{5}{w^{2}+w-6}=\frac{4}{w^{2}+7 w+12}, \] we first factor the quadratic expressions in the denominators. 1. **Factoring**: - \( w^2 + 2w - 8 = (w + 4)(w - 2) \) - \( w^2 + w - 6 = (w + 3)(w - 2) \) - \( w^2 + 7w + 12 = (w + 3)(w + 4) \) So, substituting the factored forms, the equation becomes: \[ \frac{4}{(w + 4)(w - 2)} + \frac{5}{(w + 3)(w - 2)} = \frac{4}{(w + 3)(w + 4)}. \] 2. **Finding a common denominator**: The common denominator for the left-hand side is \( (w + 4)(w - 2)(w + 3) \). Rewrite each fraction: \[ \frac{4(w + 3)}{(w + 4)(w - 2)(w + 3)} + \frac{5(w + 4)}{(w + 3)(w - 2)(w + 4)} = \frac{4(w - 2)}{(w + 3)(w + 4)(w - 2)}. \] Hence, the equation simplifies to: \[ 4(w + 3) + 5(w + 4) = 4(w - 2). \] 3. **Expanding and combining like terms**: Expanding both sides gives us: \[ 4w + 12 + 5w + 20 = 4w - 8. \] Combining like terms yields: \[ (4w + 5w + 12 + 20) = 4w - 8 \implies 9w + 32 = 4w - 8. \] 4. **Solving for \( w \)**: Subtract \( 4w \) from both sides: \[ 9w - 4w + 32 = -8, \] which simplifies to: \[ 5w + 32 = -8. \] Now, subtract \( 32 \): \[ 5w = -8 - 32 \implies 5w = -40. \] Finally, divide by \( 5 \): \[ w = -8. \] 5. **Verification**: We need to check if \( w = -8 \) does not make any denominator zero: - \( w^2 + 2w - 8 = (-8)^2 + 2(-8) - 8 = 64 - 16 - 8 = 40 \) (not zero) - \( w^2 + w - 6 = (-8)^2 + (-8) - 6 = 64 - 8 - 6 = 50 \) (not zero) - \( w^2 + 7w + 12 = (-8)^2 + 7(-8) + 12 = 64 - 56 + 12 = 20 \) (not zero) Thus, the solution is \[ \boxed{-8}. \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy